Safety of surveillance endoscopy and EUS of the esophagus after neoadjuvant chemoradiotherapy: Results from the (pre)SANO trial - Gangaram Panday, Sanjiv S.G.; Kuan Yean, Low; Bisseling, Tanya M.; Curvers, Wouter L.; van Dieren, Jolanda M.; Quispel, Rutger; Oostenbrug, Liekele E.; van der Linden, Andries; Corporaal, Sietske; Hol, Lieke; Kouw, Eva; van der Kraan, Jolein; Hazen, Wouter L.; Honing, Judith; van Lanschot, J. Jan B.; Mostert, Bianca; Nuyttens, Joost J.; van der Sluis, Pieter C.; Wijnhoven, Bas P.L.; Spaander, Manon C.W.; Lagarde, Sjoerd M. (Endoscopy International Open, 2025)
Active surveillance has been proposed for patients with esophageal cancer and a clinical complete response after neoadjuvant chemoradiotherapy (nCRT). This strategy involves repeated esophagogastroduodenoscopy (EGD) with bite-on-bite biopsies and endoscopic ultrasonography (EUS) with fine-needle aspiration (FNA) to detect tumor regrowth or residual disease. The aim of this study was to assess safety of endoscopic procedures during active surveillance.A prospective multicenter cohort including patients who were treated with nCRT for esophageal cancer and who underwent EGD with bite-on-bite biopsies and/or EUS (with fine-needle aspiration) was retrospectively analyzed. The primary outcome was the difference in number of serious adverse events (SAEs) in endoscopic procedures performed within vs. more than 3 months after nCRT. The secondary outcome was mechanical injury.In 920 patients, 2291 endoscopic procedures were performed (57% EGD combined with EUS, 39% EGD only and 4% EUS only). Of these procedures, 819 (36%) were performed more than 3 months after nCRT in 186 patients. Two gastrointestinal bleedings were reported during endoscopic procedures performed within 3 months after nCRT. One gastrointestinal bleeding and two infections were reported after 3 months following nCRT. Frequency of SAEs before and after 3 months following completion of nCRT was not significantly different (2 vs. 3, odds ratio 2.7, 95% confidence interval 0.3–32.4, P = 0.36).EGD with bite-on-bite biopsies and EUS with FNA seem to be safe during an active surveillance strategy in esophageal cancer patients after nCRT.
Keywords: Endoscopy Upper GI Tract; Barrett's and adenocarcinoma; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE); Endoscopic ultrasonography; Esophageal cancer